2020
DOI: 10.1093/hmg/ddaa086
|View full text |Cite
|
Sign up to set email alerts
|

Lowe syndrome patient cells display mTOR- and RhoGTPase-dependent phenotypes alleviated by rapamycin and statins

Abstract: Lowe syndrome (LS) is an X-linked developmental disease characterized by cognitive deficiencies, bilateral congenital cataracts and renal dysfunction. Unfortunately, this disease leads to the early death of affected children often due to kidney failure. Although this condition was first described in the early 1950s and the affected gene (OCRL1) was identified in the early 1990s, its pathophysiological mechanism is not fully understood and there is no LS-specific cure available to patients. Here we report two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 92 publications
2
16
0
Order By: Relevance
“…On the one hand, data presented in this study supports the hypothesis that some Ocrl1's functional roles are segregated within the protein primary structure (12,15,42). Specifically, that integrity of the N-terminus being mostly required for membrane remodeling functions (e.g., cell spreading (12)), while Ocrl1's C-terminal region is relevant for ciliogenesis (15).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the one hand, data presented in this study supports the hypothesis that some Ocrl1's functional roles are segregated within the protein primary structure (12,15,42). Specifically, that integrity of the N-terminus being mostly required for membrane remodeling functions (e.g., cell spreading (12)), while Ocrl1's C-terminal region is relevant for ciliogenesis (15).…”
Section: Discussionsupporting
confidence: 79%
“…Complementing the pioneering works by different authors (12)(13)(14)(15)(16)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) this study contributes to better understand Lowe syndrome as a complex disease. Here we highlight the heterogenous nature of this condition by focusing on the impact of different OCRL1 mutations on typical LS cellular phenotypes while reporting new abnormalities triggered by specific patient variants.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the reduction in insulin signaling evidenced in our experiments at the cellular level, specifically in conditions of reduction of OCRL1 function, not only would reduce megalin recycling but also would potentially decrease megalin endocytosis as pAKT is required for the efficient megalin-mediated endocytosis of albumin, a physiologically relevant ligand of the receptor present in the proximal tubule ( Silva-Aguiar et al, 2022 ). Regarding AKT activity, it has been recently found that the mTORC1 complex is inactivated in OCRL1 deficient cells ( Madhivanan et al, 2020 ), a defect that triggers a lack of nutrient-sensing ( Wang et al, 2021 ) due to mTORC1 is required for proper insulin signaling ( Saltiel and Kahn, 2001 ). Insulin signaling is also highly dependent on the cell type, something we observed in our experiments, and is associated with insulin receptor trafficking ( Iraburu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were complemented by biochemical and cell biological assays to assess the mutational impact on protein function and availability ( De Leo et al, 2016 ; Ramadesikan et al, 2021 ). Furthermore, models were prepared by various methods to gain mechanistic insight into LS such as KO/morpholino zebrafish lines ( Coon et al, 2012 ; Ramirez et al, 2012 ; Gliozzi et al, 2020 ), humanized mouse models ( Bothwell et al, 2011 ), Ocrl1-deficient cells by CRISPR ( Madhivanan et al, 2020 ) along with stable lines expressing specific variants ( Ramadesikan et al, 2021 ), and patient-derived iPSCs ( Barnes et al, 2018 ; Hsieh et al, 2018 ; Liu et al, 2020 ; Akhtar et al, 2022 ). Taken together, LS research has greatly benefitted from the assimilation of a variety of techniques and is rapidly moving towards understanding LS in a patient mutation-specific manner to better guide the design novel therapeutic approaches.…”
Section: Advances Towards the Use Of An Integrated And Updated Multid...mentioning
confidence: 99%